2010
DOI: 10.1158/1078-0432.ccr-09-1692
|View full text |Cite
|
Sign up to set email alerts
|

Death Receptor Agonists as a Targeted Therapy for Cancer

Abstract: Apoptosis is integral to normal, physiologic processes that regulate cell number and results in the removal of unnecessary or damaged cells. Apoptosis is frequently dysregulated in human cancers, and recent advancements in our understanding of the regulation of programmed cell death pathways has led to the development of novel agents to reactivate apoptosis in malignant cells. The activation of cell surface death receptors by tumor necrosis factor-related apoptosis-inducing ligand (Apo2L/TRAIL) and death recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
129
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(131 citation statements)
references
References 62 publications
1
129
0
1
Order By: Relevance
“…However, the overall antitumor activity of these antibodies is modest or limited in unselected patient populations (53,54). In this study, we found that cancer cell lines with ras or B-raf mutation showed a significantly higher response rate than those without these gene mutations (Fig.…”
Section: Discussionmentioning
confidence: 58%
“…However, the overall antitumor activity of these antibodies is modest or limited in unselected patient populations (53,54). In this study, we found that cancer cell lines with ras or B-raf mutation showed a significantly higher response rate than those without these gene mutations (Fig.…”
Section: Discussionmentioning
confidence: 58%
“…Several proapoptotic receptor agonists (PARA), including mAbs, have been developed to target this extrinsic apoptotic pathway (3,4). However, despite promising preclinical data, none of these approaches have thus far demonstrated significant clinical efficacy (5)(6)(7). Although some antibodies appear to be able to autonomously activate DR4 and DR5, many require additional cross-linking to achieve optimal activity in vitro (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, while clinical trials with TRAIL agonists have demonstrated acceptable safety and tolerability, there has been little evidence to-date of single agent efficacy. 1 However, in numerous ongoing studies, anti-TRAIL receptor agonists and soluble TRAIL are currently being evaluated in combination with standard of care therapies, and the expectation, largely based on a wealth of pre-clinical data, is that the TRAIL therapies may show efficacy in the combination setting. Thus, by analogy, it is significant that BIIB036 has demonstrated enhanced efficacy when administered in combination with a variety of standard of care agents, since BIIB036 may also require combination dosing to reveal its full potential as an anticancer therapeutic in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Among the most promising therapeutics in this category are those targeting the TNFrelated apoptosis inducing ligand (TRAIL/Apo2L) pathway, in the form of agonistic antibodies to the TRAIL receptors [TRAIL-R1 (DR4) and TRAIL-R2 (DR5)] and soluble TRAIL, all of which are currently undergoing clinical evaluation (reviewed in ref. 1).…”
Section: Introductionmentioning
confidence: 99%